Photodynamic therapy: current trends and potential future role in the treatment of bladder cancer - Kochergin, Maxim; Fahmy, Omar; Asimakopoulos, Anastasios; Theil, Gerit; Zietz, Kathleen; Bialek, Johanna; Tiberi, Eugenio; Gakis, Georgios (Multidisciplinary Digital Publishing Institute, 2024)
Bladder cancer (BC) is the 10th most common cancer in the world. The therapeutic spectrum of BC is broad and is constantly expanding. Despite the wide clinical use of photodynamic diagnosis (PTD) for BC, PDT has not been sufficiently investigated in the treatment landscape of BC. We performed an online search of the PubMed database using these keywords: photodynamic therapy, bladder cancer, urothelial carcinoma, in vivo, in vitro, cell line, animal model. Reviews, case reports, and articles devoted to photodynamic diagnostics and the photodynamic therapy of tumors other than urothelial carcinoma were excluded. Of a total of 695 publications, we selected 20 articles with clinical data, 34 articles on in vivo PDT, and 106 articles on in vitro data. The results presented in animal models highlight the potential use of PDT in the neoadjuvant or adjuvant setting to reduce local recurrence in the bladder and upper urinary tracts. Possible regimens include the combination of PDT with intravesical chemotherapy for improved local tumor control or the integration of vascular-targeted PDT in combination with modern systemic drugs in order to boost local response. We summarize available evidence on the preclinical and clinical application of PDT for urothelial carcinoma in order to explain the current trends and future perspectives.